Solution properties of poly (dimethylsiloxanes) in toluene / Maimunah Sokro and Arba'at Hassan - Sokro, Maimunah; Hassan, Arba'at (2004)
A commercial sample of liquid poly (dimethylsiloxanes) [PDMS] was fractionated, yielding five fractions of Mn ranging from 480 to 1130 g/mol and of Mw ranging from 500 to 1175 g/mol. The fractions were dissolved in toluene and characterized by vapour pressure osmometry, viscometry, differential refractometer and light scattering. Light scattering and vapour pressure measurements reveal that the fractions are monodisperse. The viscosity measurements along with vapour pressure osmometer and light scattering give the Mark-Houwink constants in toluene at 25°C as v = 1.01 and K' = 1.35 X 10-3. Others parameters, e.g. second virial coefficient, radius of gyration, unperturbed dimension, density, refractive index, coefficient of isothermal compressibility, light scattering depolarization ratio and Rayleigh ratio have also been evaluated at different temperatures.